Solve it!

Determine the sum of integers for which n 2 + 19 n + 92 { n }^{ 2 }+19n+92 is a perfect square


The answer is -19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

We wish to find n n such that n 2 + 19 n + 92 = m 2 n^{2} + 19n + 92 = m^{2} for some integer m . m. Completing the square, we then have that

( n + 19 2 ) 2 ( 19 2 ) 2 + 92 = m 2 ( n + 19 2 ) 2 + 7 4 = m 2 (n + \frac{19}{2})^{2} - (\frac{19}{2})^{2} + 92 = m^{2} \Longrightarrow (n + \frac{19}{2})^{2} + \frac{7}{4} = m^{2}

( 2 m ) 2 ( 2 n + 19 ) 2 = 7 ( 2 m + ( 2 n + 19 ) ) ( 2 m ( 2 n + 19 ) ) = 7. \Longrightarrow (2m)^{2} - (2n + 19)^{2} = 7 \Longrightarrow (2m + (2n + 19))(2m - (2n + 19)) = 7.

Since we are looking for integer solutions, we must then have that either

  • (i) 2 m + ( 2 n + 19 ) = 7 , 2 m ( 2 n + 19 ) = 1 m = 2 , n = 8 2m + (2n + 19) = 7, 2m - (2n + 19) = 1 \Longrightarrow m = 2, n = -8 ,

  • (ii) 2 m + ( 2 n + 19 ) = 7 , 2 m ( 2 n + 19 ) = 1 m = 2 , n = 11 , 2m + (2n + 19) = -7, 2m - (2n + 19) = -1 \Longrightarrow m = -2, n = -11,

  • (iii) 2 m + ( 2 n + 19 ) = 1 , 2 m ( 2 n + 19 ) = 7 m = 2 , n = 11 2m + (2n + 19) = 1, 2m - (2n + 19) = 7 \Longrightarrow m = 2, n = -11 , or

  • (iv) 2 m + ( 2 n + 19 ) = 1 , 2 m ( 2 n + 19 ) = 7 m = 2 , n = 8. 2m + (2n + 19) = -1, 2m - (2n + 19) = -7 \Longrightarrow m = -2, n = -8.

Thus the only possible values for n n are 8 -8 and 11 -11 , which sum to 19 . \boxed{-19}.

Paola Ramírez
Apr 18, 2015

n 2 + 19 n + 92 = k 2 n^2+19n+92=k^2 so the discriminant must be integer and be a perfect square.

D = 1 9 2 4 ( 1 ) ( 92 k 2 ) = 4 k 2 7 = m 2 D=19^2-4(1)(92-k^2)=4k^2-7=m^2

4 k 2 m 2 = 7 \Rightarrow 4k^2-m^2=7 so ( 2 k m ) ( 2 k + m ) = 7 (2k-m)(2k+m)=7

We get four sistem of equations:

2 k m = 1 2k-m=1 with 2 k + m = 7 2k+m=7 , and 2 k m = 7 2k-m=7 with 2 k + m = 1 2k+m=1 have as solution k = 2 k=2

2 k m = 1 2k-m=-1 with 2 k + m = 7 2k+m=-7 , and 2 k m = 7 2k-m=-7 with 2 k + m = 1 2k+m=-1 have as solution k = 2 k=-2

Then substitute and solve for n 2 + 19 n + 92 = k 2 n^2+19n+92=k^2 and get as solutions n = 11 , 8 n=-11,-8 \therefore the sum is 19 \boxed{-19}

How come you need to consider the discriminant? Where does that come from?

Josh Banister - 6 years, 1 month ago

Log in to reply

We know that b 2 { b }^{ 2 } is odd as b = 19 b=19 . So, D = b 2 4 a c { D }={ b }^{ 2 }-4ac is also odd. Now, when we take a look at the quadratic formula, b ± D 2 a \frac { -b\pm \sqrt { D } }{ 2a } , if D D is an odd perfect square , then D \sqrt { D } is a odd integer. Hence, b ± D -b\pm \sqrt { D } is an even integer. So, b ± D 2 \frac { -b\pm \sqrt { D } }{ 2 } is also an integer. That is why, the d i s c r i m i n a n t discriminant should be a perfect square in this case.

Vighnesh Raut - 6 years, 1 month ago

I solved the problem correctly , i just wanted to ask how do we get the logic that we have to multiply the eqation by 4

avn bha - 5 years, 10 months ago
Kevin Silva
Apr 24, 2015

There is a shortcut to this problem

Given that x²+19x+92= 0

Sum = -b/a Product= c/a

a=1 b=19 c=92 Sum of roots is -b/a

So the answer is -19

This method is not correct. As over here, the sum of the roots is 19 -19 for the roots as 19 ± 7 i 2 \frac { -19\pm \sqrt { 7 } i }{ 2 } . Also, only 0 0 is not a perfect square.

Vighnesh Raut - 6 years, 1 month ago

Another method is the form

x²-(r1+r2)x+(r1*r2)=0

Where r1 and r2 are the roots of the quadratic equation

Kevin Silva - 6 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...